Efficacy of topical N-acetylcysteine as a part of multicomponent treatment for severe dry eye syndrome (Ukrainian Journal of Ophthalmology, 2025)
Background: According to Tear Film and Ocular Surface Society's Dry Eye Workshop II, the precorneal tear film plays a crucial role in moisturizing the corneal surface and allowing for an optically smooth corneal surface. In addition, as a result of imbalanced secretion of the muco-aqueous phase of the tear film, the mucin layer traps shed epithelial cells, inflammatory cells, and debris to form a mucous clot within the lower conjunctival fornix. Increased mucus viscosity prevents moving mucus away via the punctum, which contributes to the development of severe dry eye syndrome (DES). Our clinical experience argues that tear replacement therapy alone can be not enough in the treatment of severe DES. N-acetylcysteine (NAC), a collagenase inhibitor, has been widely employed clinically as a mucolytic agent. Foreign literature is scant on the use of NAC as an anti-inflammatory, mucolytic, detoxicant and anti-oxidative agent in the treatment of DES.Purpose: To assess the efficacy of topical 5% N-acetylcysteine as a part of multicomponent treatment for severe DES associated with increased mucus production.Material and Methods: We reviewed records of 15 patients examined and treated for severe DES. At baseline, there was biomicroscopic evidence of mucous discharge in the lower conjunctival fornix, corneal epitheliopathy in the form of punctate fluorescein staining, and desquamated epithelium, which was consistent with severe DES.Results: At admission, mean Schirmer’s test value and tear break-up time (TBUT) were 3.4 mm (range, 2 to 6 mm) and 4.2 s (range, 2 to 8 s), respectively, and conjunctival impression cytology revealed focal epithelial degeneration. Topical 5% NAC was administered 4 times daily for 3 months as a part of multicomponent therapy for severe DES.After 3 months of topical 5% NAC, 86.6% of patients noted good tolerance to the drug and improvement of subjective symptoms, and there was biomicroscopic evidence of a reduced amount of mucus in the lower conjunctival fornix and decreased epithelial desquamation. Mean Schirmer’s test and TBUT values increased to 5.0 ± 1.7 mm (mean ± SD) and 6.4 ± 1.7 s, respectively. Conjunctival impression cytology showed the presence of mucoid substance; diffused, differentiated epithelial cells without signs of degeneration; and an adequate superficial conjunctival epithelial cell layer.Conclusion: Topical 5% N-acetylcysteine 4 times daily as a part of multicomponent treatment showed a substantial mucolytic effect for severe DES with apparent thick mucus discharge in the lower conjunctival fornix and resulted in the development of an adequate superficial conjunctival epithelial cell layer. Findings of this study allow us to recommend topical 5% N-acetylcysteine for severe DES patients with increased viscous mucous discharge in the lower conjunctival fornix.
Keywords: severe dry eye syndrome; mucin; mucous thread; N-acetylcysteine; mucolytic